2018
DOI: 10.1080/01434632.2018.1502776
|View full text |Cite
|
Sign up to set email alerts
|

‘Is there an app for that?’ Exploring games and apps among heritage language families

Abstract: View related articles View Crossmark data Citing articles: 3 View citing articles 'Is there an app for that?' Exploring games and apps among heritage language families

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 27 publications
0
20
0
2
Order By: Relevance
“…In a study on the relationship between the motivation to engage in online games and the motivation to engage with the home language (Little 2019a), background information provided by 212 participating families showed that 82% of children had a generic interest in online or mobile games, and an encouraging 78% of the families declared that children were, in principle, interested in the home language. These figures, and the resulting overlap amongst the two groups, highlight the potential affordances of the medium specifically within the home language context, although the dichotomy of children as language learners versus children as game players needs to be further explored (Little 2019a). Whitton (2013), for example, points out that the enjoyment of playing games does not necessarily correlate with the motivation to engage in games-based learning, and that online games and access to technology raise complex tensions around equity and social inclusion.…”
Section: Motivational Aspects Of Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on the relationship between the motivation to engage in online games and the motivation to engage with the home language (Little 2019a), background information provided by 212 participating families showed that 82% of children had a generic interest in online or mobile games, and an encouraging 78% of the families declared that children were, in principle, interested in the home language. These figures, and the resulting overlap amongst the two groups, highlight the potential affordances of the medium specifically within the home language context, although the dichotomy of children as language learners versus children as game players needs to be further explored (Little 2019a). Whitton (2013), for example, points out that the enjoyment of playing games does not necessarily correlate with the motivation to engage in games-based learning, and that online games and access to technology raise complex tensions around equity and social inclusion.…”
Section: Motivational Aspects Of Technologymentioning
confidence: 99%
“…Parents and children may also have very different views on the kinds of games and apps that they find motivating, desirable, or useful, leading to inter-family tensions. As a result, parents may prioritise "edutainment" games aimed at language learning (Little 2019a). These games are often thinly veiled learning apps, focusing on vocabulary learning or developing literacy skills.…”
Section: Motivational Aspects Of Technologymentioning
confidence: 99%
“…The literature on family language planning provides ample examples of parentinitiated activities, which extend along a continuum of locations and spaces, from the home to the local target diaspora community, and beyond. Reported in the literature have been the control of the home language environment (Spolsky 2009) through steering language use in the home; the provision of resources such as written paperbased and online materials and games in the home language (Eisenchlas et al 2016;Little 2018); the use of new media to communicate with community members (Hatoss 2013); or living in neighborhoods with a high demographic concentration of home language speakers (Fishman 1991).…”
Section: Infra Micro Planningmentioning
confidence: 99%
“…The metaphor facilitates the exploration of evolving, personalized, emotional connections rather than assuming a default mental position. As such, it can help to address the parental fear that if they take a more relaxed approach, the child’s bilingual identity will suffer (Little, 2018).…”
Section: Emotion Identity and Belonging In Multilingual Familiesmentioning
confidence: 99%